2020
DOI: 10.3390/microorganisms8071081
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization, Intra-Species Diversity and Abundance of Freshwater Plesiomonas shigelloides Isolates

Abstract: Molecular signatures of Plesiomonas shigelloides strain specific to pathogenic and nonpathogenic variants are not well established till present. There is a need for intra-species barcoding of P. shigelloides to aid infection control. This study aims at characterizing and assessing intra-species diversity and abundance of P. shigelloides isolated from three freshwaters in the Eastern Cape Province. The study used a Plesiomonas-specific PCR to characterize the isolates. Intra-species (dis)similarities were asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In recent years, there have been increasing reports on the pathogenicity of P. shigelloides in fishes. The pathogenic symptoms of P. shigelloides are slightly different in different fishes; this may be caused by the differences in fish species, culture environments, and strains ( 38 , 39 ). However, few studies have been conducted on the pathogenic mechanism of P. shigelloides in fishes ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there have been increasing reports on the pathogenicity of P. shigelloides in fishes. The pathogenic symptoms of P. shigelloides are slightly different in different fishes; this may be caused by the differences in fish species, culture environments, and strains ( 38 , 39 ). However, few studies have been conducted on the pathogenic mechanism of P. shigelloides in fishes ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can multiply in the intestines of fishes, damaging their organs and ultimately causing death ( 37 ). Grass carp mainly presents with redness and swelling of the body surface, liver, intestine, and anus ( 38 , 39 ). Garra rufa infected with Streptococcus agalactiae presents with surface ulceration and intestinal and hepatic lesions ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…27,41 Typeability was 81.8% where 8 isolates were untypable. Other studies reported the inability of ERIC-PCR to type some isolates of Plesiomonas shigelloides, 42 and E. coli. 43,44 At 100% similarity, ERIC gave five clusters with 18 isolates.…”
Section: Discussionmentioning
confidence: 99%